E-Commerce im Luxusmarkensegment: Die Sicht deutscher Kundinnen am Beispiel Chanel - Lina Holthaus; Carmen Horn; Jens K. Perret (Books on Demand (BoD), 2020)
– Digitalization is a set part of today's society and even luxury brands feel the increasing need of a digital presence. More than half of all consumers of luxury goods buy them online on a regular basis. The luxury fashion brand Chanel still abstains from offering their most important items in their portfolio online: fashion, jewelry and watches. In thus study the question is considered how consumers of luxury products perceive the increasing digitalization in the luxury sector and whether Chanel can remain successful with sticking to ist current strategy. The results of an empirical study reveal that as well for current Chanel customers as for future customers a strong antipathy against the increasing digitalization of luxury brands persists and they expect a critical loss in exclusivity.
urn:nbn:de:101:1-2021021900122047814260
Keywords: 380; Luxusgüter; Online-Handel; Konsumentenverhalten; Marketingmanagement; Kundenanalyse; Deutschland